Desentralisasi Asimetris: Kemiskinan Ditengah Kelimpahan Otonomi Khusus Papua - Nurmasari, Nurmasari; Al Hafis, Raden Imam (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
The main purpose of implementing asymmetric decentralization is to realize the Distribution of Power and Authority. So that each region has the opportunity to develop the existing potential and carry out governance independently and be able to realize social justice and equitable prosperity for all levels of society. However, in practice, there is often a mismatch between expectations and reality. As in Papua, which becomes an irony amid the abundance of special autonomy but poverty is a major problem. The purpose of writing this problem is to look at the problem of poverty that ensnared Papua in the midst of an abundance of special autonomy to be proud of. The method used in this paper is a literature study. The results of the analysis carried out on this problem namely as empirical evidence as we have seen together based on poverty statistics are still very concerning. This means that even though the Special Autonomy Law has stipulated systemic designs as formulated in the Act, in reality, the Act in hypothetical implementation has not been able to fulfil the objectives of the Papua Land Special Autonomy Law. For this reason, it is necessary to implement a 1. strict control mechanism for the use of the special autonomy budget; 2. Eradicating massive corruption and allocating funds for public welfare; and 3. The government's political will is needed to change budget management.Keywords: Asymmetric Decentralization, Poverty, Special Autonomy.